ANALISIS PENCATATAN DAN PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM - Wibowo, M Rizaldy; Putri, Rizqy Fadhlina; Nasution, Rahmah Yani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This study aims to determine the Recording and Preparation of Financial Statements in Brandan Donuts in accordance with SAK EMKM. This type of research is qualitative research. This study uses primary data and secondary data. Primary data obtained from interviews directly to the Owner, while secondary data obtained from data that has been processed and presented by Brandan Donuts such as financial statement data and data relating to research. Data collection techniques in this study using observation techniques, interview techniques, and documentation techniques and analysis techniques used are using data reduction, data presentation and drawing conclusions. The results showed that Brandan Donuts in recording and compilation was not in accordance with SAK EMKM, Brandan Donuts only makes profit and loss arrangements. That is because there are internal and external factors that influence it.